Efficacy of dexamethasone, salbutamol, and reduced respirable particulate concentration on aerobic capacity in horses with smoke‐induced mild asthma. (18th January 2020) - Bond, Stephanie L.; Greco‐Otto, Persephone; MacLeod, Jacqueline; Galezowski, Angelica; Bayly, Warwick; Léguillette, Renaud
Abstract: Background: Mild asthma in horses decreases racing performance and impairs gas exchange. The efficacy of treatment on performance is unknown. Hypothesis: Treatment targeting lung inflammation improves V ˙ O2 peak in horses with mild asthma. Animals: Thoroughbred polo horses (n = 12) with smoke‐induced mild asthma. Horses were exposed to increased ambient particulate matter (35.51 μg/m 3 [PM2.5 ]; day mean, centrally measured) from day −33 to 0, from bushfire smoke (natural model). Methods: Prospective, randomized, placebo‐controlled, double‐blinded clinical trial. All horses completed 3 V ˙ O2 peak tests, measuring aerobic and anaerobic variables: day 0 ‐baseline; day 16 ‐after dexamethasone (20 mg IM q24h; DEX, n = 6) or saline treatment (SALINE, n = 6), under improved ambient PM2.5 concentrations (7.04 μg/m 3 ); day 17‐15‐30mins after inhaled salbutamol (1500 μg). Bronchoalveolar lavage and mucus scoring were performed on day −8 and day 20. Linear mixed effects models were used to examine the effects of timepoint and treatment group on BAL differential cell counts, mucus scores, aerobic and anaerobic variables. Results: Horses' mucus scores improved significantly from day −8 to 20 by 1.27 ± .38 ( P = .01). There was a significant increase in V ˙ O2 peak of 15.5 ± 4.0 mL(min.kg) −1 from day 0 to 17 ( P = .002), representing an average (mean) increase in V ˙ O2 peak of 13.2%. There was no difference in V˙O2 peak between treatment groups (SALINE versus DEX) at any timepoint. Conclusions and Clinical Importance: This study highlighted the key role of improved air quality on functionally important airway inflammation. Evidence provided is central to increasing owner compliance regarding improved air quality for the treatment and prevention of mild asthma.